Poland and the Origins of the Second World War c - Shannon, Alex; Shannon, Alex; James, Chris; Fazan, Jaroslaw (Peter Lang, 2021)
This monograph deals with Polish foreign policy shortly before the outbreak of the Second World War. In tracing the diplomatic activity of foreign minister Józef Beck, it discusses six general problems: (1) the Polish political situation under the pressure of appeasement; (2) the project of Intermarium and efforts to implement it; (3) the action against Czechoslovakia and the conflict with the Soviet Union; (4) the Polish attitude towards the German concept of Gesamtlosung in Germany s relations with Poland; (5) the genesis of the Polish alliance with Great Britain; (6) the Allies military inaction after Nazi Germany s aggression. In these conditions, Poland made four key decisions: it stood against Czechoslovakia, it rejected German demands, it allied itself with the United Kingdom, and it rejected the Soviet Union s claim for the Red Army to march across Polish lands.